Sobre a acrasia em Aristóteles: sua possibilidade, a abordagem dialética e a resposta antissocrática ao problema - Mendonça, Fernando Martins (2011)
This dissertation aims to connect the various passages in which Aristotle deals with the akrasia in Nicomachea Ethics, showing that they form a clear and consistent notion of such an action. This notion is also consistent with the approach of the acrasia in the book VII 1-3, where Aristotle treats acrasia in a dialectical way. The dialectical method used, taken seriously, will lead Aristotle to save the phainomena, which are the accepted views about the acrasia, and strongly deny the Socrates thesis, that the acrasia does not exist because no one can act against the knowledge which he possesses. As a result, the proposed interpretation will stand strongly against the interpretation that attributes the cause of akrasia to ignorance of some the practical syllogism s elements.